2022
DOI: 10.1155/2022/8715777
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Post-COVID-19, Chemosensitive Function, Blood Group, and Oral Health-Related Quality of Life

Abstract: Background/Purpose. Several studies reported chemosensitive dysfunction in the olfactory and gustatory domains following coronavirus disease 2019 (COVID-19). However, the long-term convalescence period of these sensory functions and associated factors remains unknown. Hence, this study explored the correlation between post-COVID-19 conditions, chemosensitive function, blood group, and oral health-related quality of life. Materials and Methods. A cross-sectional information on demographics, symptomatic disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…More recently, some studies sought to investigate whether ABO blood types are associated with long-term symptoms presentation after COVID-19 recovery. Blood type AB was significantly associated with long-term palpitation and dizziness [ 89 ], and blood type O, with subjective loss of smell [ 90 ].…”
Section: Associations Between Abo Blood Types and Covid-19mentioning
confidence: 99%
“…More recently, some studies sought to investigate whether ABO blood types are associated with long-term symptoms presentation after COVID-19 recovery. Blood type AB was significantly associated with long-term palpitation and dizziness [ 89 ], and blood type O, with subjective loss of smell [ 90 ].…”
Section: Associations Between Abo Blood Types and Covid-19mentioning
confidence: 99%
“…Alabsi et al, 2022 [ 12 ] reported that the association between ABO blood groups and infectious diseases is not just a causal relationship; however, the literature demonstrates that blood groups have an impact on disease courses and prognosis. The authors evaluated the olfactory and gustatory disturbances and found that 62% of the patients had olfactory dysfunction, with about 14% having ageusia and 68% had some form of taste alteration.…”
Section: Discussionmentioning
confidence: 99%
“…Cronbach’s alpha of its Chinese version was 0.93, showing good reliability and validity [ 11 ]. This questionnaire evaluates seven dimensions of oral health impact, including functional limitation, physical pain, psychological discomfort, physical disability, psychological disability, social disability, and handicap, through 14 validated questions [ 12 14 ]. A 5-point Likert-like scale was used to collect answers from participants (0 stands for never occurred, 1 stands for hardly ever, 2 stands for occasionally, 3 stands for fairly often, and 4 stands for very often) [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%